People, places and identities : Themes in British social and cultural history, 1700s-1980s - Tebbutt, Melanie; Kidd, Alan J. (Book collections on Project MUSE., 2017)
This book of essays on British social and cultural history since the eighteenth century draws attention to relatively neglected topics including personal and collective identities, the meanings of place, especially locality, and the significance of cultures of association. Themes range from rural England in the eighteenth century to the urbanizing society of the nineteenth century; from the Home Front in the First World War to voluntary action in the welfare state; from post 1945 civic culture to the advice columns of teenage magazines and the national press. Various aspects of civil society connect these themes notably: the different identities of place, locality and association that emerged with the growth of an urban environment during the nineteenth century and the shifting landscape of twentieth-century public discourse on social welfare and personal morality. It is of interest that several of the essays take Manchester or Lancashire as their focus.